2018
DOI: 10.1094/mpmi-07-17-0158-fi
|View full text |Cite
|
Sign up to set email alerts
|

Phytophthora parasiticaEffector PpRxLR2 SuppressesNicotiana benthamianaImmunity

Abstract: Phytophthora species secrete several classes of effector proteins during interaction with their hosts. These proteins can have multiple functions including modulation of host physiology and immunity. The RxLR effectors have the ability to enter plant cells using the plant machinery. Some of these effectors have been characterized as immunity suppressors; however, very little is known about their functions in the interaction between Phytophthora parasitica and its hosts. Using a bioinformatics pipeline, we have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…However, little is known about RXLR effectors from P. parasitica , except PSE1, which has been reported to alter the auxin content and to promote infection (Evangelisti et al ., ). In addition, 172 candidate RXLR effectors have been identified recently in the P. parasitica genome, three of which suppress INF1‐induced cell death and enhance P. parasitica virulence (Dalio et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…However, little is known about RXLR effectors from P. parasitica , except PSE1, which has been reported to alter the auxin content and to promote infection (Evangelisti et al ., ). In addition, 172 candidate RXLR effectors have been identified recently in the P. parasitica genome, three of which suppress INF1‐induced cell death and enhance P. parasitica virulence (Dalio et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Further, characterization of this effector and its close homolog in P. infestans, Pi RxLR24 revealed that the two effectors localize to the plasma and vesicular membranes, where they associate with members of the RABA GTPase subfamily, hence interfering with vesicle tracking of the host plant (Tomczynska et al, 2018). In a separate study, three core effectors of P. parasitica PpRxLR2, PpRxLR3, and PpRxLR5 were highly expressed in N. benthamiana leaves during infection (Dalio et al, 2018). Further analysis showed that effector PpRxLR2 enhanced the virulence of P. parasitica via complete suppression of the INF-1induced PCD while effectors PpRxLR3 and PpRxLR5 suppressed host plant defenses nonetheless, it was to a less significant extent when compared with PpRxLR2.…”
Section: Do Core Rxlr Effectors Play a Role In Virulence?mentioning
confidence: 91%
“…These approaches allow large-scale identification of oomycete RxLR effector arsenals. There is a growing evidence of CREs identified in a large number of oomycetes using computational approaches (Armitage et al, 2018;Dalio et al, 2018;Pecrix et al, 2019;Rojas-Estevez et al, 2020). A typical pipeline used in mining CREs in oomycete species is illustrated in Figure 1 leading to identification of putative CREs in some oomycete species ( Figure 2).…”
Section: Do Oomycetes Harbour Core Rxlr Effectors (Cres)?mentioning
confidence: 99%
“…On the other hand, the study of susceptible plants can generate the identification of susceptibility genes, which should then be avoided in any parent or hybrid. Recently, Dalio et al (2018b) found that the effector PpRxLR2 is fundamental for the aggressiveness and virulence of P. nicotianae. The authors stated that very likely the PpRxLR2 effector targets a specific protein of the susceptible rootstock C. sunki.…”
Section: Genetic Breeding Of Citrus Rootstocksmentioning
confidence: 99%